FITOREMEDIASI MENGGUNAKAN KAYU APU (Pistia stratiotes L.) DALAM KOLAM BEKAS TAMBANG BATUBARA TERHADAP PENYERAPAN LOGAM MANGAN (Mn) DAN KADMIUM (Cd) - Purnama, Miryan Sucianti; Kusumawati, Eko; Susanto, Dwi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2018)
The aim of this research is to know the interaction that occurs on apu wood (Pistia stratiotes L.) in post-coal pool water and the ability of apu wood (Pistia stratiotes L.) on the absorption of manganese (Mn) and cadmium (Cd) from pond water post mining coal. This research use Factorial Randomized Completed Random (RAL) with 2 factors that is waste water concentration (100%, 75%, 50%, 25% and 0%) and variations in the weight of apu wood (Pistia stratiotes L.) (300 gr, 200 gr and 100 gr). The number of treatments was 20 treatment combinations. Each treatment was repeated 3 times. The data obtained were analyzed using SPSS (Statistical Product and Service Solutions) 16.0. The results show that apu wood is effective in lowering Mn and Cd metals against the pool of former coal mines. The effectiveness of Mn metal absorption by apu woods (Pistia stratiotes L.) indicated in all treatment combinations with a percentage of RE of 55.56-100% and the effectiveness of Cd metal absorption is shown in all treatment combinations with a percentage of RE of 81.81-100%.